A review of developments in process flow for supercritical water oxidation. Issue 10 (10th August 2021) - Tang, XingYing; Zheng, YouChang; Liao, ZeQin; Wang, YingHui; Yang, JianQiao; Cai, Jianjun
Abstract: Supercritical water oxidation (SCWO) is a promising technology for treating degradation-resistant organic waste. In this paper, the basic principles and technical advantages of supercritical water oxidation technology are introduced, and the research on and technical characteristics of commercial enterprises are summarized. The typical SCWO process is composed of pretreatment, pressurization, preheating, reaction, cooling, depressurization, gas-liquid-solid separation and oxidant modules. Various SCWO process schemes should be developed to accommodate site conditions, avoid corrosion, prevent salt deposition, reduce building investment and minimize operational expenses. The system could be classified in the form of heat recovery, feed pretreatment, salt separation and reactor. The application range of various process technologies was clarified, and the current research on SCWO processes was summarized.